Is There A Need To Reform The Undergraduate Medical Educational System In Pakistan? - Dr. Anila Jaleel (ziauddin University, 2024)
This is the most frequently asked questions by doctors. We were taught in traditional system of education. Are we not competent doctors? Doctors of our time are performing well internationally and nationally than why to change it? Yes there is no second opinion about it. Let's look at it in the perspective of the required competencies of the 21st century doctors, the standards of medical education and its control, the problems that the health care system is facing in developing country.